Avaliação das atividades citotóxicas de alguns complexos fosfínicos de rutênio (Células tumorais MDA-MB 231) - Lima, Benedicto Augusto Vieira (2010)
In this thesis complexes of general formula: [Ru(NS)(bipy)(PP)]PF6 (NS = 2-mercaptopyridine, 2-mercaptopyrimidine, 4,6-dimethyl-2- mercaptopyrimidine and PP = dppf, dppp, dppe); [Ru(pic)(bipy)(PP)]PF6 (pic = picolinate; PP = dppf, dppp, dppe and dppm), [RuCl(bCN)(bipy)(PP)]PF6 (bCN = benzonitrile; PP = dppf and dppe), and [RuCl(bCN)(NN)(dppb)]PF6 (NN = bipy, Mebipy and phen), were synthesised from the precursor complexes cis- [RuCl2(NN)(PP)] and characterized by the usual techniques: 1H and 31P{1H} NMR, IR, UV-Vis, molar conductimetry, elemental analysis, cyclic and differential pulse voltammetry and single-crystal X-ray diffraction (except for the compounds [Ru(pic)(bipy)(dppp)]PF6, [Ru(pic)(bipy)(dppm)]PF6 and [RuCl(bCN)(Mebipy)(dppb)]PF6, which suitable single crystal were not obtained). The 31P{1H} NMR spectras of the new compounds showed that the phosphorus atoms were more deshielded than in the correspondent precursor. The E1/2 values of the complexes containing the ligands NS, pic and bCN were higher than those observed in the precursor complexes. The complexes containing the ligand dppf presented two redox process, which were assigned to the redox pairs FeII/FeIII and RuII/RuIII respectively, according to the results of the kinetics experiments monitored by differential pulse voltammetry and 31P{1H} NMR techniques. The molar conductimetry and elemental analysis assays corroborated the proposed formula and the single-crystal X-ray diffraction study of these complexes confirmed their structures. The νCN in the complexes [RuCl(bCN)(NN)(PP)]PF6 were higher (~+8 cm-1) than that observed in the free ligand (2229 cm-1). Also, it was avaluated in vitro antitumor activity of some of the compounds synthesised herein against mammary cancer cell line (MDA-MB-231), murine sarcoma, as well as against M. tuberculosis (H37Rv); some of them presented high activity.